Impact exercises using Alnmodj educational skill to learn to throw and receive the cord with the performance of step leap in rhythmic gymnastics - Hassan, Abtisam (Journal of Physical Education, 2011)
Research is a pilot study aimed to examine the impact of different teaching methods to learn some skills in rhythmic gymnastics to the Women’s College of Basic Education / Physical Education / Mustansiriya University for the second phase. It also aimed to find out more ways influential in learning some skills in rhythmic gymnastics in order to find and detect failures of the implementation of the curriculum without disrupting the vocabulary as possible. The study included 15 women out of 18 students, the community overall study. It was concluded the following: 1. There is a positive impact of the methods used (partial, units, college) to learn the skill of throwing and receiving the cord with the performance of his leap step in rhythmic gymnastics. 2. Method outperformed the educational units on the way micro and macro skill in learning to throw and receive the cord with the performance of his mansions step in rhythmic gymnastics. 3. Outperformed the way micro-macro method to learn the skill of throwing and receiving the cord with the performance of his leap step in rhythmic gymnastics. The recommendations: 1. Emphasis on using the method of teaching units and micro-educational learning skills, especially in events that take into account individual differences and skills of the vehicle and various games. 2. Developmental courses for teachers from time to time and the other for informing them of the latest teaching methods and training on how to use it.